Impact of Nutrients on Distribution of Micrasterias Sp. In Hooghly Province, West Bengal, India - Halder, Nilu (International Journal of Environment, 2016)
In the present paper morpho-taxonomic descriptions along with the illustrations of three infraspecific taxa of genus Micrasterias C. Ag. ex Ralfs, analysis of ecological parameters and correlation coefficients between nine limnological parameters as well as the relative abundances of the genus had been described. These three taxa are Micrasterias pinnatifida var. pinnatifida fa. pinnatifida (Kütz.) Ralfs, Micrasterias tropica Nordstedt var. crassa West & West and Micrasterias foliacea var. foliacea Bailey ex Ralfs belonging to the order Zygnematales under the class Chlorophyceae. All these taxa were distributed in ponds (inland water bodies) in Hooghly district, West Bengal, India. The results of analysis of physico-chemical parameters of the ponds water revealed that lower temperature and nutrient status in respect of nitrate-nitrogen (NO3-N): phosphate (PO43-): potassium (K); higher dissolved oxygen (DO) values and, slight alkaline water prompted their occurrences, growth and diversity. The above said infraspecific taxa are new taxonomic reports from West Bengal, India. The taxonomic study explored the present biodiversity of this genus while the ecological study showed a clear picture of ecological conditions and water quality of the studied water bodies. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-2, March-May 2016 Pages 36-47